اقبال ، اقبالیات اور نصابِ تعلیم: Iqbal, Iqbaliat and Educational Curriculum - ڈاکٹر فاطمہ حسن (Tashkeel e Jadeed, 2024)
Iqbal, Iqbaliat and educational curriculum Iqbaliat is a subject of our educational curriculum which is as important in the 21st century as it was in the last century. The passage of time has kept Iqbal's thought in tune with the contemporary as such that thinking minds are constantly identifying the ways present and future generations can access the multiple dimensions of this study. Iqbal and Iqbaliat are included in the curriculum of our students from elementary school to higher education at universities. However, we need to consider how and how much Iqbaliyat plays a part in the mental development, intellectual evolution, and character building of these students. Is the new generation making full use of the topics of this thinker, who was internationally recognized as a great intellectual, and the breadth of his expression? Or just by merely making his name and status formal, his poems regurgitated in the memory of the students, it’s assumed that the service to the great poet has been done. Isn't it the case that students feel closer to other poets than Iqbal and have only devotion to the poet status of Iqbal? There are many facets and considerations that should be kept in mind while including Iqbal in the curriculum and teaching his poetry. An important question also arises about the arguments presented for the use of Allama Iqbal's greatness and his thought and philosophy.